Application of case-based learning combined with problem-based learning in standardized training of cerebrospinal fluid drainage (CBL结合PBL教学模式在脑脊液外引流规范化培训中的应用) - YIN Yating (殷亚婷); ZHEN Qin (郑琴); LIU Fang (刘芳); CHEN Lishan (陈丽珊); XUE Qiang (薛强) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of case-based learning(CBL) combined with problem-based learning(PBL) in clinical teaching and practice of cerebrospinal fluid drainage for nurses. Methods According to the sequence of training, totally 17 nurses who participated in the standardized training of cerebrospinal fluid drainage were divided into two groups: 10 cases in the control group and 17 cases in the study group. The conventional teaching model was adopted in the control group, while a combined teaching methods of CBL and PBL was used in the study group. Theoretical and practical assessment results were compared between two groups. Results Nurses in the study group had higher scores of assessment on theoretical knowledge, practical skills and health education compared with those in the control group (P＜0. 01). Conclusion The combination of CBL and PBL teaching method is effective to improve the quality of teaching and standardized training of cerebrospinal fluid drainage. It is able to inspire the nurses' initiative to learn, participate and interact actively. (目的 探讨以案例为基础的学习(CBL)结合以问题为基础的学习(PBL)教学模式在脑脊液引流规范化培训中的应用效果。方法 根据培训先后顺序不同, 将科室参与培训的护士分为对照组10例和研究组17例, 分为采用传统教学模式和CBL结合PBL教学模式进行培训。通过操作考核、理论考核等对培训效果进行评价。结果 观察组护士理论考核、操作技能和患者健康宣教评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 将CBL结合PBL教学模式应用于脑脊液引流规范化培训中, 能有效提升教学培训质量, 激发护士对教学培训的主动性、参与性与互动性。)